1991
DOI: 10.1099/00221287-137-6-1387
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic growth of halophilic archaeobacteria by reduction of fumarate

Abstract: A number of strains of halophilic archaeobacteria of the genera Halobacterium and Haloferax were able to grow anaerobically using fumarate as electron acceptor. The species showing the best anaerobic growth with fumarate were Haloferax volcanii and Haloferax denitrijicans. The two Haloarcula species tested did not show anaerobic growth enhancement with fumarate. During anaerobic growth of Haloferax trolcanii in the presence of fumarate, succinate accumulated in the medium with a stoichiometry of only 0-16-0-23… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 13 publications
0
34
0
Order By: Relevance
“…gibbonsii (Oren, 1991). The ability to reduce fumarate is not correlated with the ability to reduce nitrate, (per) chlorate, DMSO or TMAO.…”
Section: Dimethyl Sulphoxide Trimethylamine N-oxide and Fumarate As mentioning
confidence: 87%
See 3 more Smart Citations
“…gibbonsii (Oren, 1991). The ability to reduce fumarate is not correlated with the ability to reduce nitrate, (per) chlorate, DMSO or TMAO.…”
Section: Dimethyl Sulphoxide Trimethylamine N-oxide and Fumarate As mentioning
confidence: 87%
“…Some members of the Haloferax genus can reduce dimethyl sulphoxide (DMSO), trimethylamine N-oxide (TMAO) (Oren & Trüper, 1990) and fumarate using them as final electron acceptors (Oren, 1991 (Oren & Trüper, 1990). Although the bases of the DMSO and TMAO respiratory systems have not been described for any member or the domain Archaea, some studies revealed that the genetic machineries involved in two pathways are closely related in haloarchaea (Müller & DasSarma, 2005).…”
Section: Dimethyl Sulphoxide Trimethylamine N-oxide and Fumarate As mentioning
confidence: 99%
See 2 more Smart Citations
“…According to physiological and genomic studies, cultivated haloarchaea are predominantly aerobic heterotrophs (Andrei et al, 2012). There are only a few known examples of facultative anaerobic haloarchaea species capable of growth by either fermentation, or anaerobic respiration using nitrate, fumarate, dimethyl sulfoxide or trimethylamine N-oxide as terminal electron acceptors (Oren and Trüper, 1990;Oren, 1991;Antunes et al, 2008;Bonete et al, 2008;Werner et al, 2014). As these electron acceptors are present in hypersaline anoxic habitats at very low concentrations (Oren, 2011), it might appear that these facultative anaerobes cannot play a significant role in anaerobic environments.…”
Section: Introductionmentioning
confidence: 99%